Evaluating the impact of the Siyazondla Homestead Food Production Programme on the food security of selected households in the Amathole District, Eastern Cape Province, South Africa - Stevens, Joseph Benjamin (University of Pretoria, 2022)
Mini Dissertation (MAgric (Rural Development))--University of Pretoria, 2022.